Addressing New Therapeutic Strategies Using Models - Faustino, Ana; Oliveira, Paula A. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
A disease model displays pathological processes observed in human or animal diseases. The models are fundamental tools in biomedical research, and they are invaluable for providing new insights into mechanisms underlying organ function, establishing the pathophysiology of a disease, and testing potential therapeutic approaches.Models have been long used to study several diseases, including cardiovascular, oncologic, metabolic, infectious, and neurological diseases, among others. Animals or cells displaying pathological processes observed in human or animal diseases have been used as models. Moreover, mathematical models are also of great importance to disease modeling. Animal models offer the unique opportunity to investigate the function of genes and pathways and the in vivo effects of drugs, bridging the gap between basic science and the treatment of diseases. The selection of a suitable model system is a crucial step in research design. For disease modeling to be meaningful, a relevant cellular or genetic phenotype must be observed. Without the use of models, both research and clinical practice worldwide would be vastly different today.This Special Issue aimed to publish original research works or reviews with models of disease, highlighting their importance to search for new therapeutic strategies.